PENERAPAN METODE INKUIRI UNTUK MENINGKATKAN KETERAMPILAN MENULIS KARANGAN NARASI PADA SISWA SMK - Pratiwi, Lusiana (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
AbstractThis study aims to "Improving narrative writing skills using inquiry methods SMK Negeri 5 Pontianak". The method used in this research is descriptive method using classroom action research conducted with two cycles consisting of planning, implementation, observation, and reflection for each cycle. Results obtained by students on pretest or before using inquiry method the average score of 69.76. The result of writing a student narrative essay on cycle I after using mind map method of inquiry of the average value 72,14. The increase of writing result of student narrative from pretest to cycle I is 2.38. Result of student short story writing in cycle II after using method of inquiry of mind of mean value 78,33. The improvement of writing result of student narrative from cycle I to cycle II is 6.19. Then it can be concluded that classroom action research using mind map method inquiry has succeeded in improving writing skill of narrative writing to students of SMK Negeri 5 Pontianak.                                                                                      Keywords:Writing’s narrative easy, method of inquiry